A review of anesthetic techniques and outcomes following minimally invasive repair of pectus excavatum (Nuss procedure). Issue 11 (11th August 2016) - Frawley, Geoff; Frawley, Jacinta; Crameri, Joe
Summary: Background: Pectus excavatum (PE) is the most common congenital chest wall deformity, occurring in 1 : 1000 children with a male to female ratio of 4 : 1. Several procedures have been described to manage this deformity, including cartilage resection with sternal osteotomy (the Ravitch procedure) and a minimally invasive repair technique (the Nuss procedure). While initially described as a nonthoracoscopic technique, the current surgical approach of the Royal Childrens Hospital involves thoracoscopic assistance. Postoperative pain is significant in patients undergoing the pectus repair and multiple analgesic regimens have been advocated with continuous thoracic epidural infusions and opioid infusions the most common. Some authors have advocated patient‐controlled analgesia (PCA), paravertebral nerve blocks (PVNB), and wound infusion catheters as alternatives. Aims: The primary aim of this study was to assess our experience with postoperative pain and analgesia requirements associated with the minimally invasive repair of pectus excavatum in children. Methods: This is a retrospective cohort study with a contemporaneous comparison group examining patients treated between January 2005 and December 2015 for minimally invasive repair of pectus excavatum by the Nuss procedure. Results: Two hundred and seventeen patients [mean age 14.9 (sd 1.9) years] with pectus excavatum treated at the Royal Childrens Hospital between 2005 and 2015 were identified. All patients were managed with thoracic epidural analgesia and intravenous morphine infusions. The epidural was effective in the postanesthesia care unit in 97.3% (failure to place an epidural rate was 4 (1.9%); no block on awakening 0.9%). A further 4 (1.8%) were removed within 24 h. The mean morphine equivalent dose in the first 24 h was 0.8 mg·kg −1 ·day −1 . PCA was continued for a mean of 3.8 days and the total mean morphine equivalent dose was 2.2 mg·kg −1 ·day −1 . Minor complications occurred in 67 (30.9%) with postoperative nausea and vomiting in 36 patients (16.6%) and urinary retention requiring an indwelling catheter in 40 patients (18.4%). Conclusion: An epidural‐based analgesic regime is associated with low pain scores and few acute complications. The continuation of morphine analgesia after the first postoperative day is common but associated with an increased incidence of urinary retention and nausea and vomiting. Abstract :